Determinan Return Saham Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman - Parlindungan Parlindungan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine the effect of Return on Assets on stock returns in food and beverage companies on the Indonesia Stock Exchange. To determine the effect of Return On Equity on Stock Returns in food and beverage companies on the Indonesia Stock Exchange. and beverages on the Indonesia Stock Exchange. This research approach uses an associative quantitative approach. The population used in this study is the financial statements. The total population of food and beverage companies is 51 companies and the sample is 11 food and beverage companies listed on the IDX. The data analysis used in this research is quantitative data using classical assumption tests, multiple regression, and hypothesis testing. Based on the results of the study, there is a significant effect of ROA on stock returns in food and beverage companies listed on the IDX. There is a significant effect of ROE on stock returns in food and beverage companies listed on the IDX. There is a significant effect of NPM on stock returns in food and beverage companies listed on the IDX. There is a significant effect of ROA, ROE, and NPM on stock returns in food and beverage companies listed on the IDX.